Numerical Studies of Optical Bistability of Absorptive Type - Jurisova, Eliska; Mullerova, Jarmila (Communications - Scientific letters of the University of Zilina, 2011)
Theoretical analysis is presented to search for the purely absorptive optical bistability in a Fabry-Perot cavity filled with a saturable absorber. A simple model of singlet absorption is used on numerically solving the relationships between the input and output light fields. The proposed model corresponds well to organic compounds considered as novel optical materials with third-order optical nonlinearities. The effects of saturable absorber parameters on the output light characteristics are studied and purely absorptive optical bistabilities are shown numerically to search for bistable behaviour. The simulated results are indications for promising applications in optical switches for all-optical communication networks.